Luminescence of amorphus dielectrics induced with high-energy electrons - Романовский, С.К.; Уваров, В.Л. (Radiotekhnika, 2016)
The main features of optical radiation of the amorphous dielectrics exposed to accelerated electron beam (cathodoluminescence- CL) have been described. It is shown, that the CL intensity is defined by dynamics of the deep traps filling with the electrons. The three main pathways of CL have been marked out: by direct condensation of non-equilibrium electrons from the conduction band into the deep traps (fluorescence), with their preliminary localization at the shallow traps and also, as a result of the charge recombination (phosphorescence).Within a two-level model of traps, the former two processes are described with the first-order kinetic equations, when the latter with the second-order one. The expressions obtained for dynamics of the CL intensity are agreed with the experimental data. Possibility of the CL application for on-line diagnostics of the product processing mode at the industrial radiation installations with the electron accelerators is shown.